Plan de marketing para la comercialización de huevos de codorniz de la pre asociación Q` Dornitos del cantón Quevedo - Bustamante Bobadilla, Karina Melissa (2016)
Marketing Plan for Association Q 'Pre Dornitos Quevedo Canton, allowed to establish through the study of market fundamentals such as preference and frequency of consumption of quail eggs compared to other alternatives, showing the behavior of actual and potential consumers of the product; the predisposition of the highest percentage of the representative sample who would agree to include in their diet eating quail eggs is also reflected. It is important to highlight the importance of the nutritional value of quail egg, displayed in the table presented in nutritional research development; this constitutes another relevant for most of the respondents responded agree with the commercialization of quail eggs through the Agricultural Association Pre Dornitos Q 'appearance. It is considered a strength that the Pre Dornitos Q 'Association, is in the process of legalization, which gives a certain formality to the project for development; It was achieved also identify certain weaknesses such as; poor access to information on quail egg producers; so the limited knowledge on markets and marketing channels; and in terms of market opportunities seen in potential growth, ranking second in the consumption of bird eggs. As such, it is considered that there are expectations that establish that the project is viable and feasible. The most relevant results obtained in this investigation established the following conclusions: The market study on both actual and potential consumers of quail eggs, found that the increased frequency of consumption is reflected away from home. Consumer preference bird eggs in the canton Quevedo, shows that the highest percentage corresponds to chicken eggs, quail eggs followed. The largest number of respondents said they would be willing to include in their diet eating quail eggs. The largest proportion of respondents agree with the commercialization of quail eggs through the Q Association Pre Dornitos Quevedo Canton.